Kata Sapaan Bahasa Jawa di Desa Bukit Payung Kecamatan Bangkinang Kabupaten Kampar - Risma Artika; Alber Alber (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study is meant to explain and look into how people in Bukit Payung Village, which is part of Bangkinang District in Kampar Regency, use different types of greetings, both those based on family relationships and those that are not. This research uses a qualitative method and focuses on describing things in detail. The data were collected through interviews and then analyzed using the Miles and Huberman interactive model, which is based on the greeting theory proposed by Syafyahya et al., (2000). The results show that there are 35 greeting terms, which include 27 terms used for greeting family members and 8 terms used for greeting people who are not family. Family greetings for relatives include both extended and nuclear family members, while greetings not based on family relationships cover religion, traditions, and general topics. How people greet each other depends on how close they are to each other. The unique part of this research is looking at both kinship and non-kinship greetings in the Javanese transmigrant community, especially in Bukit Payung Village, Bangkinang District, Kampar Regency.